The prologue and the fi rst stasimon of Oedipus at Colonus: a comparative study - Pérez Lambás, Fernando (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2017)
In this paper we analyze the fi rst stasimon of the tragedy Oedipus at Colonus of Sophocles based on the verses 16 to 18 of the prologue. The comparison between both passages may be important in the extent that the ἄλσος described in the prologue is introduced like a place, signifi cant from a dramatic point of view, which is developed poetically in the fi rst stasimon. Both descriptions have several aspects in common that may help us to understand better the nature of this sacred forest and the dramatic purpose of the verses 16-18 of the prologue, which tend to schedule the description of the fi rst stasimon.
Keywords: ἄλσος; prologue; fi rst stasimon; Oedipus at Colonus.